2020
DOI: 10.1371/journal.pone.0243550
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nanoliposomes containing HER2/neu (P5+435) peptide and evaluation of their immune responses and anti-tumoral effects as a prophylactic vaccine against breast cancer

Abstract: HER2/neu is an immunogenic protein inducing both humoral and cell-mediated immune responses. The antigen-specific cytotoxic T lymphocytes (CTLs) are the main effector immune cells in the anti-tumor immunity. To induce an effective CTL specific response against P5+435 single peptide derived from rat HER2/neu oncogene, we used a liposome delivery vehicle. In vivo enhancement of liposome stability and intracytoplasmic delivery of peptides are the main strategies which elevate the liposome-mediated drug delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Reducing the QoL in patients is a common side effect of breast cancer. 3 - 5 In a study, it was shown that breast cancer patients who have sleep problems, sadness and fatigue before chemotherapy, experience a lower quality of life during treatment than other patients who do not have these symptoms. 6 HRQoL is a multidimensional conception that includes the social, physical and mental aspects of a person’s health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the QoL in patients is a common side effect of breast cancer. 3 - 5 In a study, it was shown that breast cancer patients who have sleep problems, sadness and fatigue before chemotherapy, experience a lower quality of life during treatment than other patients who do not have these symptoms. 6 HRQoL is a multidimensional conception that includes the social, physical and mental aspects of a person’s health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Ivermectin is known as a drug with a wide range of pharmacological properties, including antimicrobial, anticancer, and antiviral effects. [18][19][20][21][22] Ivermectin is mostly used for onchocerciasis treatment and can be effective against Enterobius vermicularis, Ascaris lumbricoides, Trichuris trichiura, and Strongyloides stercoralis. [23][24][25][26] Besides, recent studies have shown the antiviral effects of Ivermectin on SARS-CoV-2, HIV-1 (human immunodeficiency virus), Avian Influenza type A, Newcastle disease, yellow fever, and West Nile virus.…”
Section: Ivermectinmentioning
confidence: 99%
“…DOPE was used to enable the fusion of liposomes, and presentation of antigens via phase transition induced in the acidic pH of endosomal compartments. Stronger immune responses with CTLs and tumor regression were detected in vivo [166,167]. ; TLR (Toll-like receptor); EPC (1,2-dioleoyl-sn-glycero-3-ethylphosphocholine); OVA (B16F10-OVA is a murine melanoma cell line expressing the chicken ovalbumin gene); gp70 RNA (Moloney murine leukemia virus); WES (whole-exome sequencing).…”
Section: Peptide Vaccinesmentioning
confidence: 99%